Metabolic and Amino Acid Alterations of the Tumor Microenvironment - Stepka, Petr; Vsiansky, Vit; Raudenska, Martina; Gumulec, Jaromir; Adam, Vojtech; Masarik, Michal (Current medicinal chemistry, 2021)
Metabolic changes driven by the hostile tumor microenvironment surrounding cancer cells and the effect of these changes on tumorigenesis and metastatic potential have been known for a long time. The usual point of interest is glucose and changes in its utilization by cancer cells, mainly in the form of the Warburg effect. However, amino acids, both intra- and extracellular, also represent an important aspect of tumour microenvironment, which can have a significant effect on cancer cell metabolism and overall development of the tumor. Namely, alterations in the metabolism of amino acids glutamine, sarcosine, aspartate, methionine and cysteine have been previously connected to the tumor progression and aggressivity of cancer. The aim of this review is to pinpoint current gaps in our knowledge of the role of amino acids as a part of the tumor microenvironment and to show the effect of various amino acids on cancer cell metabolism and metastatic potential. This review shows limitations and exceptions from the traditionally accepted model of Warburg effect in some cancer tissues, with the emphasis on prostate cancer, because the traditional definition of Warburg effect as a metabolic switch to aerobic glycolysis does not always apply. Prostatic tissue both in a healthy and transformed state significantly differs in many metabolic aspects, including the metabolisms of glucose and amino acids, from the metabolism of other tissues. Findings from different tissues are, therefore, not always interchangeable and have to be taken into account during experimentation modifying the environment of tumor tissue by amino acid supplementation or depletion, which could potentially serve as a new therapeutic approach.
Keywords: Neoplasms; cancer-associated fibroblasts; nádory; nádorová transformace buněk; nádorové mikroprostředí; Cancer metabolism; Cell Transformation, Neoplastic; tumor microenvironment; Tumor Microenvironment; lidé; Amino Acids; Warburg effect; lactate; aminokyseliny; glykolýza; Glycolysis; amino acids; Humans